Defending Indian Philosophy from the Criticisms of Stace - Bayazid, G M (Philosophy and Progress, 2024)
In his, A Critical History of Greek Philosophy, W. T. Stace denies to give Indian schools of thought a philosophical status. He gives three reasons for that—(1) Indian thoughts have practical motivation, (2) instead of rational explanation, it is content with symbolism, and (3) India lies outside the mainstream human civilization. In the defense of Indian philosophy, these three arguments have been countered in this paper from different perspectives. It has been shown that these arguments are rooted in scientism, extreme idealism, and ethnocentrism respectively. Stace has also argued that philosophy has four leading traits—(1) discussing the universe as a whole, (2) generalizing sciences, (3) idealism, and (4) non-practical motivation. For a proper defense, it has been shown that Indian systems share those traits. At the end, a conclusive remark has been given. It has been remarked that Stace’s case is an example of ethnocentric bias and racism. It has also been suggested that the interaction of the philosophies of different civilizations is necessary for the very sake of philosophy. Though this is not the first endeavor to defend Indian philosophy, the literature review (conducted by the author) suggests that Stace’s arguments haven’t been criticized separately. Philosophy and Progress, Vol#73-74; No#1-2; Jan-Dec 2023 P 281-314